Application of hazard analysis and critical control points (HACCP) to the processing of compost used in the cultivation of button mushroom - Pardo, José Emilio; Zied, Diego Cunha [UNESP]; Alvarez-Ortí, Manuel; Peñaranda, Jesús Ángel; Gómez-Cantó, Carmen; Pardo-Giménez, Arturo (My University, 2017)
Purpose: Guarantee the product protection and correction of errors, to improve the costs derived from quality defects and to reduce the final over control. Methods: In this paper, the Hazard Analysis and Critical Control Points system is applied to the processing line of compost used in the cultivation of mushrooms and other edible cultivated fungi. Results: From all stages of the process, only the reception of spawn (stage 1), raw materials (stage 3) and composting Phase II—pasteurization and conditioning (stage 7) has been considered as Critical Control Point. The main hazards found were the presence of pathogenic bacteria (stages 1 and 3), the high content in heavy metals (step 3), the use of unauthorized pesticides or doses above the permitted (stage 3), the presence of unauthorized organic matter (stage 3), the contamination by contact with the compost of Phase I (stage 7), and the wrong distribution of compost (stage 7). Conclusions: The implementation of this knowledge will allow the composting plants to control the quality and safety of their products, in order to provide safe compost to the mushroom producing industries.
Keywords: Compost security; Cultivated mushrooms; Hygiene; Quality; Self-control